Interstitial pulmonary fibrosis with and without associated collagen vascular disease: results of a two year follow up. Issue 12 (December 1992) - Agustí, C; Xaubet, A; Roca, J; Agustí, A G; Rodriguez-Roisin, R
Abstract : BACKGROUND: Interstitial pulmonary fibrosis is a disease with a highly variable clinical course. To ascertain if an inadequate selection of patients might explain part of this variability, two different groups of patients with interstitial pulmonary fibrosis, those with the "lone" form of the disease (LIPF) and those with associated collagen vascular disorders (AIPF), were studied separately. METHODS: Twenty consecutive patients (nine with LIPF and 11 with AIPF) were included. Their clinical and radiographic findings and results of pulmonary function tests, gallium-67 lung scanning, and cellular analysis of bronchoalveolar lavage fluid were compared at diagnosis. Moreover, the evolution of LIPF and AIPF was contrasted after a follow up of two years, both groups having received a similar treatment regimen of corticosteroids. RESULTS: At enrollment, patients with LIPF and AIPF were of similar age, and had similar symptoms and derangement of lung function, but patients with LIPF presented with finger clubbing, more obvious radiographic abnormalities, and a greater percentage of eosinophils in bronchoalveolar lavage fluid. Two years later, patients with LIPF had significantly decreased FVC, FEV1, TLC, TLCO, and PaO2. By contrast, lung function remained unaltered in patients with AIPF. Similarly, when the percentage change from entry to the study was compared, patients with LIPF showed a significant decrease in FVC, FEV1, and PaO2. CONCLUSIONS: Unlike the patients with AIPF, those with LIPF showed a deterioration in lung function and developed further restrictive impairment and poorer gas exchange. This has implications in their clinical management.